Deep-level diversity in entrepreneurial teams and the mediating role of conflicts on team efficacy and satisfaction - Stephanie Schoss; Diemo Urbig; Malte Brettel; René Mauer (International Entrepreneurship and Management Journal, 2020)
Team start-ups have substantial advantages over solo start-ups, but teams often do not live up to their potential due to conflicts creating unfavorable team dynamics. Based on an experiment with 665 individuals in 133 randomly composed teams participating in a new-venture simulation, we found team members' deep-level characteristics that trigger motivations to act, i.e., achievement motivation and leadership orientations, to be particularly important sources of task conflicts. We found that diversity in leadership orientation reduces conflicts because not all team members can lead at the same time. Unlike hypothesized, we found that diversity in achievement motivation also reduces conflicts, for which, ex-post, we explore potential reasons. Furthermore, we demonstrate that the mediating task and relationship conflicts differently affect team outcomes due to their different nature of task-relatedness: while task conflicts affect task-related team efficacy and may escalate into relationship conflicts, relationship conflicts directly affect team satisfaction, but not team efficacy. Further emphasizing the importance of a motivational basis of conflicts, we found that individuals' general self-efficacy, a more belief-related construct, affects team outcomes only through team efficacy, but not via conflicts.
Keywords: 650; Entrepreneurial teams; Deep-level diversity; Task conflicts; Relationship conflicts; Team efficacy; Team satisfaction; Experiment